Education and homeschooling: controversies (Práxis Educativa, 2020)
This paper, in essay format and oriented towards the philosophy of education, discusses the issue of homeschooling from the perspective of socialization processes and the formative potential inherent to interaction. Its purpose is to question the possible implications of a limited education regarding the process of meeting, opening and coexistence with each other. Therefore, the theoretical contributions of Mead and Habermas are used, especially the notions of socialization and individuation, symbolic interaction and communicative action. With the help of Waldenfels, the dimension of strangeness from the other is explained, which challenges the subject to openness and the recognition of alterity. Finally, the paper shows that situations of restriction of education to the family environment, or homeschooling, denote the loss of the formative potential inherent to interaction and encounter with others, meaning a narrowing of the educational process.Keywords: Education. Alterity. Homeschooling.